2009
DOI: 10.1038/gene.2009.49
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine and chemokine receptor expression analysis in target organs of acute graft-versus-host disease

Abstract: Acute graft-versus-host disease (aGVHD) is a major complication after allogeneic bone marrow transplantation (allo-BMT), and infiltration of donor leukocytes into aGVHD target organs is partially orchestrated by chemokines. Using a murine BMT model, the expression of 30 chemokines or chemokine receptors in the lung, liver, gut and tongue was analyzed using real-time PCR at 1, 2, 3 and 6 weeks after BMT during the development of clinical aGVHD and target organ histopathology. CXCL9-11 expression was linked to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 92 publications
3
55
0
Order By: Relevance
“…Several groups have explored and identified the role of various chemokines in T-cell migration and trafficking to target tissues in the GVHD process. 14,36,48 In line with these observations, we have found that expression levels of CXCL1, CXCL9, CXCL11 and CCL5 were increased after allo-SCT. Interestingly, whereas the expression of CXCL1 and CXCL13 was higher in the liver, CXCL9, CXCL11 and CCL5 were more highly expressed in the kidney.…”
Section: Discussionsupporting
confidence: 76%
“…Several groups have explored and identified the role of various chemokines in T-cell migration and trafficking to target tissues in the GVHD process. 14,36,48 In line with these observations, we have found that expression levels of CXCL1, CXCL9, CXCL11 and CCL5 were increased after allo-SCT. Interestingly, whereas the expression of CXCL1 and CXCL13 was higher in the liver, CXCL9, CXCL11 and CCL5 were more highly expressed in the kidney.…”
Section: Discussionsupporting
confidence: 76%
“…100 Expression of CXCR3 or CCR2 on donor CD8 ϩ T cells targets these cells to the gut and liver but not lung. [101][102][103][104] These results suggest that strategies that influence T-cell migration, particularly to GVHD target organs, may offer promise for reducing GVHD target organ-specific injury, although the redundancy of chemokines and their receptors may hinder clinical efficacy in the context of GVHD prevention or therapy. As such, targeting lymphocyte/integrin interaction may be a more promising way to explore.…”
Section: Acute Gvhd Pathophysiology 4331 Blood 12 November 2009 ⅐ Vomentioning
confidence: 97%
“…The liver expression of CCL3-CCL5 was associated with an increase of CCR1 and CCR5. The hepatic expression of CCL2, CCL8, CCL12 and their receptor CCR2 were also increased [28]. CCR5 is a CC chemokine receptor.…”
Section: The Role Of Cytokinesmentioning
confidence: 98%